Labour Diversity and Domestic Firm’s Productivity in Kenya - Mugendi, Charles N.; Ocharo, Kennedy N. (My University, 2015)
This study attempted to empirically examine the effect of labour diversity on firm’s productivity in Kenya. To achieve this objective primary data was collected from various firms. Thereafter analysis was done using Feasible Generalized Least Square method (FGLS). According to the study, firms that had more labour diversity in terms of skills and gender were more productive. But ethnic diversity had no impact on productivity. This is a crucial finding given the ongoing debate on the role of gender in development. Additionally, other variables like size of the firm and research & development expenditure had an influence on firms’ productivity.